IDENTIFICATION OF JATAKA STORIES IN THE BUDDHIST CANDIS OF CENTRAL JAVA: A Semiotic Study of Reliefs in the Candi Sojiwan, Mendut, and Borobudur - Santacitto, Sentot; Firnadi, Aryanto; Indramayapanna, Rakay (Jurnal Pencerahan, 2018)
The story of the past life of Buddha Gotama has become one of the most important discussions in Buddhist philosophy. The stories of his life are recorded in the Pāli Canon mainly in the Jātaka texts (birth stories of the Buddha). Jataka stories have obtained popularity in ancient times in Buddhist countries such as India, Sri Lanka, Myanmar, Thailand and even Indonesia. Its reputation which appeared in many Jātaka stories is being put into Buddhist art and architecture. In Indonesia, Jataka stories are found among reliefs on the walls of Candi Buddhist, such as Candi Sojiwan, Mendut and Borobudur. However, at present time there are no books that try to discuss Jātaka story carved on the walls of these temples thoroughly and systematically. This research tries to identify reliefs of Jātaka found in three Candi that are located in Central Java namely Candi Sojiwan, Mendut and Borobudur. The theory used in this research is Semiotics theory of Charles Shanders Pierce. This theory is used to interpret the signs contained in the reliefs of the Candi by using triangle of meaning ie., interpretants (researchers), objects (reliefs on the three Candis) and signs. Within the sign there are three things being analized namely icons, indexes and symbols. In relation to the icon, the researchers identify the images on the relief as they are. Then, in indexes, the researchers interpret images that have been identified in accordance with the existing context. For example, the icon that reveals the images of humans, crowns, and jewelry show that someone who wore the crown and jewelry was identified as a high standing one or even a king. Because these three Candis are Buddhist temples, the symbols given are of course tend to be of Buddhist context. When certain reliefs are identified to have represented certain Jātaka stories, they are considered objects that symbolize the Jātaka story. In this research there are 109 panel reliefs from three Candis that have been successfully studied. Among 109 panel reliefs there are 38 panels indentified as representing Jātaka stories. In Candi Sojiwan, 20 panel reliefs are found, but only 8 panels have been identified as telling the story of Jātaka. From 45 panels, 15 panel reliefs in Candi Mendut have been found to represent the Jātaka story. Meanwhile, 230 panel reliefs in Borobudur temple are then reduced to 44 panels and 15 are successfully identified to have links to Jātaka stories.